Criminal and criminological aspects of domestic violence in Switzerland (Archives of Criminology, 2023)
The article is about domestic violence in Switzerland. The problem of domestic violence is presented from a criminal and criminological perspective. The phenomenon of domestic violence in the Swiss experience has not been studied or described in the Polish literature on criminal law and criminology, so the main aim of the study was to expand the knowledge about crimes related to family violence committed in Switzerland and to present a picture of this type of crime. The dogmatic and statistical methods were used. The first part of the study presents a historical outline of the problem. This section also describes selected criminological theories explaining the causes of violent behaviour and various definitions of domestic violence. The second part of the article contains a description of the crimes from the Swiss Criminal Code which have been registered by the local police as being committed in connection with domestic violence. The third part of the article presents the criminological aspects of domestic violence in Switzerland. This section describes the structure, size and dynamics of crime related to domestic violence. Information on the relationship between the victim and the perpetrator of the crime is also presented in this part. The article also includes information on the proportion of domestic offences in the total number of all violent crimes and information on the perpetrators of crimes of domestic violence (e.g., their age and gender).